HUBUNGAN ANTARA INTENSITAS ESTRUS DENGAN KONSENTRASI ESTRADIOL PADA SAPI ACEH PADA SAAT INSEMINASI (Relation between Estrous Intensity and Estradiol Concentration on Local Cattle during Insemination) - Mauridatun Ramli; Tongku Nizwan Siregar; Cut Nila Thasmi; Dasrul Dasrul; Sri Wahyuni; Arman Sayuti (Universitas Syiah Kuala, 2016)
This study aims to determine the relationship between the intensity of estrus and estradiol concentrations during insemination on local cattle. Ten cows were divided into two groups with each group consist of five cows with category: aged 5-8 years, weight 150-250 kg, clinically healthy, and not pregnant. Plasma samples for examination of the hormone estradiol concentrations were collected during insemination time from jugular vein. Prior to the collection of plasma samples, whole cow were estrus synchronized using prostaglandin F2 alpha (PGF2α) and Ovsynch protocol. The PGF2α were injected twice at intervals of 11 days. Examination of estradiol hormone concentration was performed with enzyme-linked immunosorbent assay (ELISA) using estradiol commercial kits. The results of this study indicate that statistically there is no relationship between estrous intensity and estradiol concentration.